The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/e23091187
|View full text |Cite
|
Sign up to set email alerts
|

High-Rate Continuous-Variable Quantum Key Distribution with Orbital Angular Momentum Multiplexing

Abstract: The secret key rate is one of the main obstacles to the practical application of continuous-variable quantum key distribution (CVQKD). In this paper, we propose a multiplexing scheme to increase the secret key rate of the CVQKD system with orbital angular momentum (OAM). The propagation characteristics of a typical vortex beam, involving the Laguerre–Gaussian (LG) beam, are analyzed in an atmospheric channel for the Kolmogorov turbulence model. Discrete modulation is utilized to extend the maximal transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The atmospheric turbulence channel can be characterized by the effective transmittance and the channel excess noise. The effective transmittance of different OAM states propagating in the atmospheric channel can be derived from the correct propagation probability of the initial mode detected by the receiver, namely [37,38]…”
Section: Properties Of the Atmospheric Turbulence Channelmentioning
confidence: 99%
See 1 more Smart Citation
“…The atmospheric turbulence channel can be characterized by the effective transmittance and the channel excess noise. The effective transmittance of different OAM states propagating in the atmospheric channel can be derived from the correct propagation probability of the initial mode detected by the receiver, namely [37,38]…”
Section: Properties Of the Atmospheric Turbulence Channelmentioning
confidence: 99%
“…The channel excess noise may originate from multiple sources, such as from imperfect modulation, intensity fluctuations of the used lasers, background light, and so on [41,42]. In our work, we will focus on the crosstalk noise among different OAM modes caused by the atmospheric turbulence, which can be expressed as [38]…”
Section: Properties Of the Atmospheric Turbulence Channelmentioning
confidence: 99%
“…It can be implemented in the discrete-variable scheme and continuousvariable scheme (CVQKD) [6,7], and the latter has the advantages of a high secret key rate (SKR) and low cost. Long-distance transmission [8] and high SKR [9,10] are the two critical goals of CVQKD, which are limited by the practical transmission loss of the quantum channel, excess noise, and reconciliation efficiency [11,12]. Therefore, maintaining high reconciliation efficiency [13,14] and low excess noise is a major obstacle to the realization of remote CVQKD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, owing to the special helical phase and hollow light field of the OAM beam, OAM can be applied to micro-control technologies in the microscopic world, such as optical tweezers and micromotors [ 9 ]. As an independent degree of freedom for wireless and quantum communications, OAM can be used to achieve a higher communication capacity through the simultaneous transmission of multiple orthogonal OAM mode vortex beams [ 10 , 11 , 12 , 13 ]. It has even been suggested that telescopes equipped with OAM diagnostic instruments can be made to detect rotating black holes [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%